Revisit intention in conservation areas: How destination image mediates perceived risk and constraint in Bromo Tengger Semeru National Park - Maulana Iksan; Intan Tri Annisa (International Journal of Applied Sciences in Tourism and Events, 2026)
This study was conducted to examine the effects of perceived risk and perceived constraints on tourists' revisit intention, with destination image as a mediating variable, in TNBTS tourism in Central Jakarta, and to review it from an Islamic point of view. The sample consisted of 169 tourists from Central Jakarta who had visited one of TNBTS's destinations. The sampling technique used is purposive sampling. Data were collected using a survey method with questionnaires. The data were analysed using SPSS and Partial Least Squares Structural Equation Modelling (PLS-SEM). The results showed that (1) perceived risk has no significant effect on revisit intention (2) perceived constraints have a negative and significant effect on revisit intention (3) perceived risk has a positive and significant effect on destination image (4) perceived constraints have a negative and significant effect on destination image (5) destination image has a positive and significant effect on revisit intention (6) destination image mediates the relationship between perceived risk and revisit intention (7) destination image can mediate the effect of perceived constraints on revisit intention. Thus, future researchers can directly interview TNBTS tourists to obtain respondents who meet the criteria and achieve satisfactory results.